The Economic Impact of EU Guarantees on Credit to SMEs – Evidence from CESEE Countries - Pierfederico Asdrubali; Simone Signore (European Investment Fund (EIF), 2015)
This paper estimates the economic impact at final beneficiary level of the Multi-Annual Programme for enterprises and entrepreneurship EU SME Guarantee Facility in Central, Eastern and South-Eastern European (CESEE) Countries in the period 2005-2012. Data on SME beneficiaries has been collected from administrative records and enriched with information on firms' financial accounts taken from the Orbis database. The paper combines propensity scores and difference-in-differences estimation in order to evaluate the effect of having received a MAP-guaranteed SME loan on firm performance (employment, production, profitability and factor productivity) against a control group of comparable firms. Our results offer several insights. We find that the EU SME Guarantee Facility in the CESEE region had, on average, a significant positive effect on firms' employment: beneficiary firms were able to increase their workforce by 17.3%, compared to the control groups, within the first 5 years following the issuance of the guaranteed loan. Moreover, by the fifth year after the signature date, the turnover of MAP beneficiaries had increased by 19.6%, compared to non-beneficiary companies. However, MAP beneficiaries faced a temporary setback in productivity, with respect to their peers, an effect that could be due to allocative inefficiencies following the MAP-induced increase in their production factors. Such gap was, however, partially absorbed over the medium run. By breaking down our sample by country, signature year, size and age classes, we observe that micro and young SMEs have benefited the most from MAP-guaranteed loans in terms of economic additionality. Overall, our findings suggest that the EU SME Guarantee Facility has been successful in bringing significant positive effects on beneficiary firms in CESEE Countries.
Keywords: 330